Abundance and infestation of rice stem borer in North Malaysia - Nur Atiqah Mohd Khari,; Suhaila Ab Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The abundance and infestation of rice stem borer were monitored in MADA regions with the influence of weather parameters. The determination of the rice stem borer percentage infestation was recorded by dead heart (DH) and whitehead (WH) symptoms. In four regions of MADA area observations, a higher infestation of rice stem borer was observed during rice planting season one (7.1%) compared to rice planting season two (3.9%) on average. Both damage symptoms of the rice stem borer, DH, and WH were observed higher during the rice planting season one. The highest infestation of rice stem borer during season one was observed in Pendang with 18.60%. From the weather parameters recorded, a high infestation of rice stem borer occurred at 80.0% (RHmax), 8.2 °C of temperature differences (Tdiff), and a lower amount of rainfall (0.6 mm). The high infestation in Pendang in season one was influenced by the lower value of RH, higher range of temperature, and lower amount of rainfall compared to season two. Chilo polychrysus was the most abundant species of rice stem borer found in Region 1 and Scirpophaga incertulas were abundantly found in Region 2, 3, and 4.